Potential risk factors and outcomes of infection with multidrug resistance among diabetic patients having ulcers: 7 years study. Issue 1 (January 2019) - Zubair, Mohammad; Ahmad, Jamal
Abstract: Diabetes Mellitus is characterized as a hyperglycemic condition, which results due to alteration in the secretion of insulin or action of insulin. The development and spread of microorganisms is known as a key health concern, and such cases are growing drastically in hospitals and communities. Therefore, the study aims to determine the potential risk factors and infection outcomes among diabetic patients with multi drug resistance, who are suffering from foot ulcerations. A prospective cohort analysis was carried out among 192 diabetic patients admitted in the Rajiv Gandhi Centre for Diabetes and Endocrinology of Jawaharlal Nehru Medical College Hospital, Aligarh Muslim University, India. The patients having ulcer or ulcers in their foot during the period December 2008–June 2015 were included in the study. The results indicated the rate of resistance to CS and PC, which was 56.7% and 51.9%. The most common isolates included Escherichia coli (25.5%), Staphylococcus aureus (22.6%), and Klebsiella sp (5.4%). A total of 121 isolates from 278 were associated with the MDR. Furthermore, anaerobic isolates were also included in the study which included Peptostreptococcus spp, Propionibacterium spp, Clostridium perfringens, Eggerthella lenta, and Bacteroides ureolyticus . Ulcer was found among majority of patients with the duration of 1 month; whereas, the ulcer size was also the major risk factor for diabetic patients. Therefore, it is concluded that there is a major need for surveillance of resistant bacteria to reduce the risk of major complications.